Bioindustry ethics - Finegold, David (Elsevier Academic Press, 2005)
This book is the first systematic, detailed treatment of the approaches to ethical issues taken by biotech and pharmaceutical companies. The application of genetic/genomic technologies raises a whole spectrum of ethical questions affecting global health that must be addressed. Topics covered in this comprehensive survey include considerations for bioprospecting in transgenics, genomics, drug discovery, and nutrigenomics, as well as how to improve stakeholder relations, design ethical clinical trials, avoid conflicts of interest, and establish ethics advisory boards. The expert authors represent multiple disciplines including law, medicine, bioinformatics, pharmaceutics, business, and ethics.